PROGRAM MALU MENGANGGUR (STUDI IMPLEMENTASI DI KABUPATEN LAMPUNG TIMUR) (Administratio, 2018)
A program called "Malu Menganggur" is an independent workforce program aims to empower communities from local government of East Lampung regency by providing specialized training to create products and its market home-based products by forming industry groups. The purpose of this study is to analyze the implementation of "Malu Menganggur" program and to analyze the obstacles in the implementation of "Malu Menganggur" program by the Department of Cooperatives of Small and Medium Enterprises and Manpower of East Lampung regency in Jabung and Purbolinggo sub-districts. The method used in this research was qualitative approach. The data collection techniques were conducted through interviews, observation and documentation. The results showed that the implementation of "Malu Menganggur" program has not been well implemented, especially in the sub-district of Jabung. The limited implementation of the program was due to the uneven accomplishment of the program. The implementation of Malu Menganggur program, in Jabung sub-district did not develop because people merely focused on the funds and not being independent. While in Purbolinggo sub-district, the community was very enthusiastic although with circumstances of limited facilities and limited knowledge about the concept of self-employment. The inhibiting factors in the implementation of Malu Menganggur program was devided into internal and external factors. The internal factors was the limited funding from Local Government, there was no special fund allocated for Malu Menganggur program. While the external factors included: the lack of public awareness and community participation in the implementation of the program, the less awareness of the community to be open minded about the concept of self-employment. There are several suggestions for this research: it is neecessary to hold socialization of advanced self-employment, to build a good coordination among the Activity Unit Management, and the local government must allocate special fund for Malu Menganggur program.